Characterization, Stability, and In Vitro Release Evaluation of Carboxymethyl Chitosan Coated Liposomes Containing Fish Oil. Issue 7 (15th June 2015) - Wang, Qianqian; Lv, Shun; Lu, Jianfeng; Jiang, Shaotong; Lin, Lin
Abstract Fish oil was extracted and refined from Nile tilapia viscera. Uncoated liposomes (un‐L) and carboxymethylchitosan (CMCS)‐coated liposomes (CM‐L) containing fish oil were prepared, and their characteristics, stability, and release in vitro were studied. The CMCS coating increased the mean diameter of liposomes but there was no effect on entrapment efficiency. The surface structure and characteristics of liposomes were determined. The Fourier transform infrared spectroscopy showed that the hydrogen bonding formed between the CMCS and the carbonyl region of the liposomes' bilayer. The transition temperature of CM‐L was higher than un‐L. The stabilities of un‐L and CM‐L stored at 4 °C were better than 25 °C. Moreover, the CM‐L was significantly more stable than un‐L when stored at 25 °C. The release behaviors of un‐L and CM‐L were governed by 2 distinct stages and the first‐order model was the most suitable model for the whole release procedure. The diffusion and erosion may be the main release mechanisms for the full controlled release of fish oil from the liposomes. This study can provide theories and practice information for further applications of fish oil from tilapia viscera.